Archetypal dialogues: goddesses as a source of inspiration for stage creations (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In August 2024, Dr. Luciana Aires Mesquita began the postdoctoral project "Mitoludens between Goddesses and Sambaquis," as a FAPESC Fellow, under the supervision of Dr. Maria Brígida de Miranda in the Graduate Program in Performing Arts at the State University of Santa Catarina (PPGAC/UDESC). Over the course of a year, the partnership resulted in several academic and artistic activities, such as performances, lectures, and film productions made available on web platforms. In this interview with Miranda, Mesquita reflected on the field of archetypal psychology created by James Hillman and the experience of creating stage productions based on the study of goddesses and gods from Greek mythology.
Keywords: mythology; archetypes; feminism; deities; stage criation